Technical diagnosis of cuban school swimmers backstroke - Hery Leyva González Leyva González; Imaday Núñez González; Axel Cancio Milian (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The teaching-learning process of swimming, in the conditions of Cuba, comprises several stages; the first initiation, with a duration of three to four years. Once the ten years have passed, the perfection stage begins, and finally, to the high performance of sports in adolescence. Although their improvement process favors the formation of specific motor skills in the Back stroke technique of junior swimmers, they do not show similarity in their underwater strokes with the theoretical model of technical efficiency. The following work intends from a field study and, using the empirical observation, to diagnose the mechanics of swimming of the movement of arms of the school back stroke swimmers in order to point out the technical patterns used and to identify, the main potentialities and errors of these.